Sistem Informasi Pemantauan Inventory Stock Opname Berbasis Web Pada Sbu-Teh Kemasan PTPN VI - Fazillah , M. Rio; Devitra , Joni (Jurnal Manajemen Sistem Informasi, 2022)
Perkebunan Nusantara VI has a sub-section, namely SBU Teh Packaging which has the task of handling the recording of inventory data, purchases of goods, requests for operational activities for all parts, to reporting and the number of requests each month. The problem that occurs is that inventory data processing is still done manually, using Microsoft Excel. This causes the control of goods data to be disorganized, resulting in frequent duplication of goods names. Even in making reports, the warehouse officer takes a long time and the results obtained are not accurate. Based on the problems faced, a web-based inventory control information system is needed that can assist the process of managing and monitoring inventory stock-taking data. The purpose of this research is to design a prototype of a web-based inventory control information system using a system modeling tool, namely UML. The result of this research is a prototype design of a web-based inventory control information system that can be applied by PT. Perkebunan Nusantara VI, especially SBU Teh Packaging to help expedite the management and monitoring of inventory stock taking data.